PERAN INSTRUMEN SUKUK DALAM PEMBIAYAAN PEMBANGUNAN NASIONAL: PERSPEKTIF KEUANGAN PUBLIK SYARIAH - FITRI ROHIMAH; ANYA REGISTA CAHYANI; FIRMAN HIDAYATULLAH (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2025)
Sukuk as an Islamic financial instrument has developed into one of the significant financing alternatives in supporting national development, especially within the framework of Islamic public finance. This research aims to analyze the strategic role of sukuk instruments in financing infrastructure development and other public sectors in Indonesia. Using a descriptive qualitative approach based on a literature study, this research examines literature, legislation, and the practice of implementing sukuk both at the national and global levels. The results show that sukuk not only serve as a shariah-compliant source of financing, but also expand public participation in development investment, improve fiscal transparency, and attract foreign investment through instruments such as green sukuk. The study also highlights the innovative application of digital sukuk by fintech platforms such as Danantara as a breakthrough in the technology-based agriculture sector. Thus, sukuk has great potential to become a key pillar in financing sustainable and inclusive development in the modern economic era.